2016
DOI: 10.3892/mmr.2016.5889
|View full text |Cite
|
Sign up to set email alerts
|

Rho kinase II interference by small hairpin RNA ameliorates 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced parkinsonism in mice

Abstract: Novel therapeutic targets are required for the treatment of Parkinson's disease (PD). Previous studies suggest that the Rho/Rho-associated, coiled-coil-containing protein kinases (ROCKs) signaling pathway may be a promising therapeutic target in PD. To elucidate the importance of ROCKII in the pathogenesis of dopaminergic (DA) neuron loss and to investigate the efficacy of ROCK inhibitors in PD, ROCKII expression in the substantia nigra (SN) of mice was silenced through the injection of a lentivirus-based smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Several synthetic and natural substances, as summarized in Table 1, are utilized to attenuate dopaminergic neuron loss through suppressing TLR signaling pathway and NF-κB (Café-Mendes et al, 2017;Cheng & Zhu, 2019;Li et al, 2018;Ling et al, 2019;Lv et al, 2019;Xu et al, 2017;Yang et al, 2019;Yu et al, 2016;Zhang & Xu, 2018 ;Zhang et al, 2016 It has been demonstrated that aggregated α-synuclein by binding to CD36 on microglia, which by recruiting Fyn kinase can activate protein kinase C-delta (PKC-δ), thereby propagating translocation of NF-κB p65 subunit to the nucleus. In the nucleus, p65 subunit enhances expression of IL-1β and NLR family pyrin domain containing 3 (NLRP3) inflammasome (Panicker et al, 2019) (Figure 1).…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several synthetic and natural substances, as summarized in Table 1, are utilized to attenuate dopaminergic neuron loss through suppressing TLR signaling pathway and NF-κB (Café-Mendes et al, 2017;Cheng & Zhu, 2019;Li et al, 2018;Ling et al, 2019;Lv et al, 2019;Xu et al, 2017;Yang et al, 2019;Yu et al, 2016;Zhang & Xu, 2018 ;Zhang et al, 2016 It has been demonstrated that aggregated α-synuclein by binding to CD36 on microglia, which by recruiting Fyn kinase can activate protein kinase C-delta (PKC-δ), thereby propagating translocation of NF-κB p65 subunit to the nucleus. In the nucleus, p65 subunit enhances expression of IL-1β and NLR family pyrin domain containing 3 (NLRP3) inflammasome (Panicker et al, 2019) (Figure 1).…”
Section: Inflammationmentioning
confidence: 99%
“…Several synthetic and natural substances, as summarized in Table 1, are utilized to attenuate dopaminergic neuron loss through suppressing TLR signaling pathway and NF‐κB (Café‐Mendes et al., 2017; Cheng & Zhu, 2019; Li et al., 2018; Ling et al., 2019; Lv et al., 2019; Xu et al., 2017; Yang et al., 2019; Yu et al., 2016; Zhang & Xu, 2018 ​; Zhang et al., 2016).…”
Section: Evidence Into Involvement Of Nf‐κb Family In Pdmentioning
confidence: 99%
“…ROCK activation has been shown to play a major role in the microglial pro-inflammatory response, including migration of microglia into the inflamed areas [ 24 , 51 , 52 , 53 ]. Our research group and others have shown that ROCK inhibitors have neuroprotective effects against dopaminergic degeneration in PD models [ 42 , 54 , 55 ], and that inhibition of the microglial pro-inflammatory response plays a major role in the neuroprotective effect [ 23 , 42 , 56 , 57 ]. More recently, we showed that the ROCK inhibitor fasudil inhibits the dyskinetic behavior induced by L-DOPA in PD models, which is mediated by inhibition of the neuroinflammatory response [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although one of the published studies has reported that the shRNAs decreased the expression of α-synuclein and attenuated dopamine neuron degeneration in rat PD model induced with 1-methyl-4-phenyl 1,2,3,6-tetrahydropyridine (MPTP) ( Liu et al, 2014 ; Zhang et al, 2016 ), however, other techniques, such as decreasing inflammation via class II transactivator or caspase-1 inhibition by shRNA, have also been tried instead of directly targeting SNCA ( Li et al, 2020 ). In addition, shRNAs targeting nuclear receptor related 1 (Nurr1) or Src homology region 2 (SH2)-containing protein tyrosine phosphatase 2 (Shp2) were developed as a viable method for treating levodopa-induced dyskinesias ( Sellnow et al, 2015 ).…”
Section: Therapeutic Development Of α-Synuclein Targeting Sirnamentioning
confidence: 99%